Using Targeted Phonon Excitation to Modulate Thermal Conductivity of Boron Nitride - Pan, Dongkai; Li, Tianhao; Wan, Xiao; Zong, Zhicheng; Qin, Yangjun; Yang, Nuo (Chinese physics letters, 2025)
Recent advancements in thermal conductivity modulating strategies have shown promising enhancements to the thermal management capabilities of two-dimensional materials. In this article, both the iterative Boltzmann transport equation solution and the two-temperature model were employed to investigate the efficacy of targeted phonon excitation applied to hexagonal boron nitride (hBN). The results indicate significant modifications to hBN’s thermal conductivity, achieving increases of up to 30.1% as well as decreases of up to 59.8%. These findings validate the reliability of the strategy, expand its scope of applicability, and establish it as a powerful tool for tailoring thermal properties across a wider range of fields.